Translation and validation of the East Asian Acculturation Measure (EAAM) among Myanmar migrants in Thailand - Htet Shwe Wah Oo; Ratsiri Thato; Nyan Win Phyo (Belitung Nursing Journal, 2024)
Background: Acculturation provides a framework for exploring the health behaviors of ethnic minority or cultural groups. Research on the acculturation level and patterns of Myanmar migrants is crucial since there is ample evidence that acculturation promotes health-promoting behaviors. However, no Myanmar version has undergone cross-cultural validation. Objective: This study aimed to translate the original East Asian Acculturation Measure (EAAM) into the Myanmar version (EAAM-M) and investigate its psychometric properties. Methods: The validation study was conducted on a sample of 200 Myanmar migrants in three factories in Bangkok, Thailand, by a multistage random sampling method from August to September 2023. Brislin’s back translation technique was applied to convert the original EAAM into its modified version, EAAM-M. The reliability, content validity, and construct validity of the EAAM-M were examined, and confirmatory factor analysis (CFA) was employed to test the appropriateness of the model that underpins the EAAM-M structure. Results: The average age of the participants was 38.39 years (SD = 5.56), and 68% of participants reported they earned less than 9000 baht. In terms of how long they stayed in Thailand, slightly over half (52.5%) did so for 1-5 years. Nearly half of them (46%) cannot communicate at all regarding their proficiency in speaking Thai. The score regarding the comparability of language and similarity of interpretability between the original EAAM and the EAAM-M was satisfactory. The overall alpha reliability of the EAAM-M was 0.76. Based on the CFA, the measurement model was well fit, with acceptable goodness-of-fit values (Chi-square test of model fit (p = 0.05), CMIN/df = 1.70 (X2 = 624.931, df = 366), RMSEA = 0.02, CFI = 0.98, and SRMR = 0.06). The validity and reliability of the factors were affirmed through appropriate factor loadings and satisfactory levels of composite reliability (0.942) and average variance extracted (0.538). Conclusion: The EAAM-M is a reliable and valid instrument to measure the acculturation patterns of Myanmar migrants. It is beneficial for scholars across various disciplines, including health professionals and nurses, to deliver culturally tailored care for migrants.